Základní koncepty Pierra Bourdieu: pole – kapitál – habitus - Michal Růžička; Petr Vašát (AntropoWebzin)
The authors argue that the work of Pierre Bourdieu (1903-2002) can be understood as composing of three pillars: (1) „epistemologization“ of social science, (2) attempt to overcome classical philosophical dualisms of Western thought, and (3) integration of scientific rigour into political engagement. This paper focuses on the second pillar by introducing to the reader the most fundamental concepts of Pierre Bourdieu´s sociology: concepts of social field, forms of capital, and habitus. Emphasis is given on how are these concepts intertwined and how it is not possible to understand one without the others.